Analysis of the Spontaneous Emission Limited Linewidth of an Integrated III–V/SiN Laser. Issue 6 (18th March 2022) - Chow, Weng W.; Wan, Yating; Bowers, John E.; Grillot, Frédéric
Abstract: This article describes a calculation of the spontaneous emission limited linewidth of a semiconductor laser consisting of hybrid or heterogeneously integrated, silicon and III–V intracavity components. Central to the approach are a) description of the multi‐element laser cavity in terms of composite laser/free‐space eigenmodes, b) use of multimode laser theory to treat mode competition and multiwave mixing, and c) incorporation of quantum‐optical contributions to account for spontaneous emission effects. Application of the model is illustrated for the case of linewidth narrowing in an InAs quantum‐dot laser coupled to a high‐ Q Q SiN cavity. Abstract : The maturating of III–V laser technology intensifies the exploration of complex optical configurations based on integrating III–V and silicon photonics. This article describes a laser theory, beyond the customary quasi‐mode approximation for treating resonator outcoupling, for understanding the physics underlying spectral narrowing to Hz‐level, spontaneous‐emission limited lasing linewidth.